Stable water splitting using photoelectrodes with a cryogelated overlayer - Byungjun Kang; Jeiwan Tan; Kyungmin Kim; Donyoung Kang; Hyungsoo Lee; Sunihl Ma; Young Sun Park; Juwon Yun; Soobin Lee; Chan Uk Lee; Gyumin Jang; Jeongyoub Lee; et al. (Nature Communications, 2024)
Abstract Hydrogen production techniques based on solar-water splitting have emerged as carbon-free energy systems. Many researchers have developed highly efficient thin-film photoelectrochemical (PEC) devices made of low-cost and earth-abundant materials. However, solar water splitting systems suffer from short lifetimes due to catalyst instability that is attributed to both chemical dissolution and mechanical stress produced by hydrogen bubbles. A recent study found that the nanoporous hydrogel could prevent the structural degradation of the PEC devices. In this study, we investigate the protection mechanism of the hydrogel-based overlayer by engineering its porous structure using the cryogelation technique. Tests for cryogel overlayers with varied pore structures, such as disconnected micropores, interconnected micropores, and surface macropores, reveal that the hydrogen gas trapped in the cryogel protector reduce shear stress at the catalyst surface by providing bubble nucleation sites. The cryogelated overlayer effectively preserves the uniformly distributed platinum catalyst particles on the device surface for over 200 h. Our finding can help establish semi-permanent photoelectrochemical devices to realize a carbon-free society.